Windfall Apples: Tanka and Kyoka - Richard Stevenson (Mingling Voices, 2010)
The venerable tanka and her upstart cousin kyoka mingle with Kerouac's American pop haiku in five-liner imagist poems and linked sequences. In Windfall Apples, Richard Stevenson mixes east and west with backyard barbecue and rueful reflection.